MBA Feedback (2017)
The MBA program has been steady in admissions, course enrollment, and continues to be financially self-sustaining. After initial years of struggling, the Goleta location is now developing a sustainable student population. Although the national market for MBA programs seems to be down, the MBA in Thousand Oaks has benefited greatly from the double MS Biotechnology degree program. Also, a change of schedule to the traditional semester may help with successfully attracting more international students. One of the challenges for the MBA has been administrative load for the Director, and the need for more tenure track faculty. As a result, EU has committed funding for a new tenure track position which will also take on the Director responsibilities. Overall, the MBA is a solid special sessions degree program which continues to serve the local community.